ARTIFICIAL INTELLIGENCE AND SECURITY IN NIGERIA: A SOCIO-TECHNICAL ANALYSIS OF OPPORTUNITIES AND CONSTRAINTS - Anulika Ndoh, Juliet; Emmanuel Iwuh, Chudi; Chibuzo Ugochukwu, Stanley (African Journal of Social and Behavioural Sciences, 2026)
This study critically examines the role of artificial intelligence (AI) in Nigeria's security architecture through a socio-technical lens, analysing the nexus between technological opportunities, institutional constraints, and governance challenges. Rather than providing a broad overview, this research demonstrates that effective AI adoption requires integrating technological systems with strong institutions, ethical frameworks, and human capacity development, rather than relying on technology deployment alone. Using secondary data sources, including peer-reviewed journals (2021–2026), policy documents, government publications, and international reports, the study employs qualitative content analysis to examine Nigeria's current AI-security landscape. Findings reveal that while AI tools such as facial recognition, predictive policing, and cyber defence systems offer significant potential, Nigeria's adoption remains constrained by poor digital infrastructure, inadequate policy frameworks, and weak institutional capacity. The study concludes that successful AI integration requires a holistic approach that combines technological investment with governance reforms, capacity building, and ethical safeguards. The research contributes to existing scholarship by moving beyond techno-optimism to examine how failures of socio-technical systems explain Nigeria's lagging AI adoption in security despite the urgent need.